2003
DOI: 10.1099/mic.0.26007-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation by 13C-NMR and tricarboxylic acid (TCA) deletion mutant analysis of pathways for succinate formation in Saccharomyces cerevisiae during anaerobic fermentation

Abstract: NMR isotopic filiation of 13 C-labelled aspartate and glutamate was used to explore the tricarboxylic acid (TCA) pathway in Saccharomyces cerevisiae during anaerobic glucose fermentation. The assimilation of [3-13 C]aspartate led to the formation of [2,3-13 C]malate and [2,3-13 C]succinate, with equal levels of 13 C incorporation, whereas site-specific enrichment on C-2 and C-3 of succinate was detected only with [3-13 C]glutamate. The non-random distribution of 13 C labelling in malate and succinate demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
111
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 39 publications
11
111
2
Order By: Relevance
“…For the organic acid catabolism, only the level of Ald5p was slightly elevated, whereas the Acs1p and Ald4p levels were reduced. In the TCA cycle, the effect of anaerobiosis was only visible for the levels of Aco2p as being raised 2.4 times, and of Cit3p, Fum1p, Kgd2p, Lsc1p, Lsc2p and the YJL045w protein product as being reduced more than two times under anaerobiosis, which is in good agreement with a reduced activity of the TCA cycle in the absence of oxygen [33]. Mitochondrial protein levels for the detected members of the respiratory chain complexes III, IV and V were all reduced under anaerobic conditions.…”
Section: Anaerobic Versus Aerobic Mitochondrial Protein Quantificationsupporting
confidence: 66%
“…For the organic acid catabolism, only the level of Ald5p was slightly elevated, whereas the Acs1p and Ald4p levels were reduced. In the TCA cycle, the effect of anaerobiosis was only visible for the levels of Aco2p as being raised 2.4 times, and of Cit3p, Fum1p, Kgd2p, Lsc1p, Lsc2p and the YJL045w protein product as being reduced more than two times under anaerobiosis, which is in good agreement with a reduced activity of the TCA cycle in the absence of oxygen [33]. Mitochondrial protein levels for the detected members of the respiratory chain complexes III, IV and V were all reduced under anaerobic conditions.…”
Section: Anaerobic Versus Aerobic Mitochondrial Protein Quantificationsupporting
confidence: 66%
“…Interestingly, genes YJL045W (similar to succinate dehydrogenase gene SDH1) and SDH2 show respective expression levels 7.5 and 1.7 times higher than those seen with ICV 16. It has been reported that during fermentation this cycle is not active, but two branches are functional (one oxidative from pyruvate to at least ␣-cetoglutarate and one reductive in the opposite sense), and there is a complete inhibition of the succinate dehydrogenase complex (8). Moreover, in ICV 27 there are higher mRNA levels of genes involved in the mechanisms for directing cytosolic NADH to the mitochondrial respiratory chain (NDE2 and GUT2) and, although to a lesser extent, in acetylcoenzyme A (CoA) metabolism and transport, ␤ oxidation, a Values shown correspond to the interval found in at least three independent vinifications carried out with each one of the strains.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, quantitative knowledge of the metabolic origins of ␣-keto acids may provide new insights regarding the regulation of the formation of fermentation products. Indeed, the formation of amino acid precursors from glucose affects not only the carbon balance but also yeast energetic and redox states through the demand for ATP, NAD, and NADPH cofactors (19)(20)(21)(22)(23). In turn, the redox and energetic status of the cells controls the distribution of fluxes through the CCM.…”
Section: Discussionmentioning
confidence: 99%
“…The ␣-keto acids cluster in two groups. First, pyruvate, oxaloacetate, and ␣-ketoglutarate are redirected toward the CCM, underlying the strong interaction of nitrogen metabolism with carbon, energetic, and redox metabolisms (19)(20)(21)(22)(23). Other compounds, including ␣-ketoisocaproate (KIC), ␣-ketoisovalerate (KIV), ␣-ketobutyrate (KIB), ␣-ketomethylvalerate, 3-indolepyruvate, and phenylpyruvate, are subsequently assimilated through the Ehrlich pathway.…”
mentioning
confidence: 99%